2017
DOI: 10.18632/oncotarget.21937
|View full text |Cite
|
Sign up to set email alerts
|

Proteogenomic characterization and integrative analysis of glioblastoma multiforme

Abstract: Glioblastoma multiforme (GBM), the most aggressive and lethal primary brain tumor, is characterized by very low life expectancy. Understanding the genomic and proteogenomic characteristics of GBM is essential for devising better therapeutic approaches.Here, we performed proteomic profiling of 8 GBM and paired normal brain tissues. In parallel, comprehensive integrative genomic analysis of GBM was performed in silico using mRNA microarray and sequencing data. Two whole transcript expression profiling cohorts we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…For example, a correlation of only 17% was found between mRNAs and proteins in lung adenocarcinoma [ 28 , 34 ]; in prostate cancer, the correlation between gene expression and protein levels is also poor to moderate [ 35 ]. Song et al [ 36 ] performed proteomic profiling of eight GBs and their paired normal brain tissues and afterwards assessed overlap with RNA gene expression profiling from GEO and TCGA datasets of GBs. They found a correlation of only 2% between the differentially expressed proteins and genes from microarray.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a correlation of only 17% was found between mRNAs and proteins in lung adenocarcinoma [ 28 , 34 ]; in prostate cancer, the correlation between gene expression and protein levels is also poor to moderate [ 35 ]. Song et al [ 36 ] performed proteomic profiling of eight GBs and their paired normal brain tissues and afterwards assessed overlap with RNA gene expression profiling from GEO and TCGA datasets of GBs. They found a correlation of only 2% between the differentially expressed proteins and genes from microarray.…”
Section: Discussionmentioning
confidence: 99%
“…Proteogenomic profiling of GBM tissues showed high expression of CD44 [23] and recent GBM systematic analysis further supported CD44 as a GBM cell surface antigen [26].…”
Section: Identifying Existing Drugs Targeting Gbm Signature and Cd44 mentioning
confidence: 79%
“…3). For tissue proteomics, we found several studies that performed comparative GBM vs. normal brain tissues proteome profiling [11,[20][21][22][23]. However, some of these studies either identified only limited number of proteins or the data are not downloadable.…”
Section: Identification Of Gbm Cell-surface Signature By Integration mentioning
confidence: 99%
“…Mass spectrometry analysis of ve GBM cell lines revealed the upregulation of EGFR, CD44, PTPRJ, SLC1A5, F2R, and TSPAN6 proteins in these samples [12], whereby the expression level of these proteins were in concordance with our transcriptomics data analysis ( Figure 3). For tissue proteomics, we found several studies that performed comparative GBM vs. normal brain tissues proteome pro ling [11,[20][21][22][23]. However, some of these studies either identi ed only a limited number of proteins or the data are not downloadable.…”
Section: Resultsmentioning
confidence: 99%